2011
DOI: 10.3126/jnps.v31i2.4065
|View full text |Cite
|
Sign up to set email alerts
|

Guillain Barre Syndrome: Major Cause of Acute Flaccid Paralysis in Children and Adolescents of Nepal

Abstract: Introduction. Guillain Barre Syndrome (GBS) is a post infectious polyneuropathy involving mainly motor but sometimes sensory and autonomic nerves. It is an acquired disease of the peripheral nerves that is characterized by rapidly progressing paralysis, areflexia and albumino-cytological dissociation in CSF. Methodology: Prospective, descriptive, observational, hospital based study was carried out to find out the clinico-epidemiological features of GBS including existing treatment modalities and its outcome. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 13 publications
2
6
0
Order By: Relevance
“…Among the children with GBS, preceeding viral illness was found in 75% children in form of diarrhea and respiratory tract infec on similar to the study of Sharma KS et al 14 . Complica ons of GBS were no ced in 50% children in the form of respiratory failure (50%) and autonomic failure (25%) with improvement seen in 25%, which is comparable to studies by Sharma KS et al The mean Glasgow Coma Scale in our study was 9.53±4.27.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Among the children with GBS, preceeding viral illness was found in 75% children in form of diarrhea and respiratory tract infec on similar to the study of Sharma KS et al 14 . Complica ons of GBS were no ced in 50% children in the form of respiratory failure (50%) and autonomic failure (25%) with improvement seen in 25%, which is comparable to studies by Sharma KS et al The mean Glasgow Coma Scale in our study was 9.53±4.27.…”
Section: Discussionsupporting
confidence: 78%
“…2011) showed GBS as the major leading cause of AFP in children 8,12,13,14 . In this study, we had a total of only 4(9.3%) children with GBS while in a similar clinico-epidemiological study done at BPKIHS by Sharma KS et al, 90% were GBS 14 . Studies by McKhann GM et al and Morris M et al also had GBS as the most common cause 12,15 .…”
Section: Discussionmentioning
confidence: 99%
“…The annual global incidence rate of GBS is one to four cases per 100,000 people. GBS is a post-infectious polyneuropathy that mainly affects the motor nerve branches [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Majority of patients improved with supportive treatment alone, in this study after 60 days follow up more than 75% cases full recovered or have only mild disability, the 18% cases have moderate to severe disability, and 4% of patients with GBS have died ( Table 5). In a study the rate recovery after 3 months reported 50% and the rate of death was 7.4% [32]. The differences may be due to low age of our patients that were 15 years old or smaller.…”
Section: Discussionmentioning
confidence: 59%